Appendectomy versus non-operative treatment for acute uncomplicated appendicitis in children: study protocol for a multicentre, open-label, non-inferiority, randomised controlled trial. Issue 1 (18th May 2017) - Hall, Nigel J; Eaton, Simon; Abbo, Olivier; Arnaud, Alexis P; Beaudin, Marianne; Brindle, Mary; Bütter, Andreana; Davies, Dafydd; Jancelewicz, Tim; Johnson, Kathy; Keijzer, Richard; Lapidus-Krol, Eveline; et al.
Abstract : Background: Appendectomy is considered the gold standard treatment for acute appendicitis. Recently the need for surgery has been challenged in both adults and children. In children there is growing clinician, patient and parental interest in non-operative treatment of acute appendicitis with antibiotics as opposed to surgery. To date no multicentre randomised controlled trials that are appropriately powered to determine efficacy of non-operative treatment (antibiotics) for acute appendicitis in children compared with surgery (appendectomy) have been performed. Methods: Multicentre, international, randomised controlled trial with a non-inferiority design. Children (age 5–16 years) with a clinical and/or radiological diagnosis of acute uncomplicated appendicitis will be randomised (1:1 ratio) to receive either laparoscopic appendectomy or treatment with intravenous (minimum 12 hours) followed by oral antibiotics (total course 10 days). Allocation to groups will be stratified by gender, duration of symptoms (> or <48 hours) and centre. Children in both treatment groups will follow a standardised treatment pathway. Primary outcome is treatment failure defined as additional intervention related to appendicitis requiring general anaesthesia within 1 year of randomisation (including recurrent appendicitis) or negative appendectomy. Important secondary outcomes will be reported and a cost-effectiveness analysis will be performed. The primary outcome will be analysed on a non-inferiority basis using a 20% non-inferiority margin. Planned sample size is 978 children. Discussion: The APPY trial will be the first multicentre randomised trial comparing non-operative treatment with appendectomy for acute uncomplicated appendicitis in children. The results of this trial have the potential to revolutionise the treatment of this common gastrointestinal emergency. The randomised design will limit the effect of bias on outcomes seen in other studies. Trial registration number: clinicaltrials.gov: NCT02687464 . Registered on Jan 13th 2016.